2021
DOI: 10.3390/ijms222312839
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Predictors of Malignancy in IPMN: A Review of the Literature

Abstract: Pancreatic cystic lesions are increasingly detected in cross-sectional imaging. Intraductal papillary mucinous neoplasm (IPMN) is a mucin-producing subtype of the pancreatic cyst lesions arising from the pancreatic duct system. IPMN is a potential precursor of pancreatic cancer. The transformation of IPMN in pancreatic cancer is progressive and requires the occurrence of low-grade dysplasia, high-grade dysplasia, and ultimately invasive cancer. Jaundice, enhancing mural nodule >5 mm, main pancreatic duct di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 109 publications
0
21
1
Order By: Relevance
“…In the Fukuoka guideline 2017, an increased serum CA 19‐9 level is one of the “worrisome features” suggesting malignancy. The sensitivity of both CA19‐9 and CEA for IPMA degeneration is reported to be high, around 90%, but their specificity is not high, around 40% and 6.1%, respectively 16 . In the present study, both CA19‐9 and CEA were not significantly suggestive of malignancy in univariate analysis, which may be due to the small number of cases in the present study and the low specificity.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In the Fukuoka guideline 2017, an increased serum CA 19‐9 level is one of the “worrisome features” suggesting malignancy. The sensitivity of both CA19‐9 and CEA for IPMA degeneration is reported to be high, around 90%, but their specificity is not high, around 40% and 6.1%, respectively 16 . In the present study, both CA19‐9 and CEA were not significantly suggestive of malignancy in univariate analysis, which may be due to the small number of cases in the present study and the low specificity.…”
Section: Discussioncontrasting
confidence: 78%
“…The sensitivity of both CA19-9 and CEA for IPMA degeneration is reported to be high, around 90%, but their specificity is not high, around 40% and 6.1%, respectively. 16 In the present study, both CA19-9 and CEA were not significantly suggestive of malignancy in univariate analysis, which may be due to the small number of cases in the present Abbreviations: BMI, body mass index; CAR, CRP-albumin ratio; HGD, high grade dysplasia; HRS, high risk stigmata; IPMA, intraductal papillary mucinous adenoma; IPMC, intraductal papillary mucinous carcinoma; NLR, neutrophil-to-lymphocyte ratio; SUVmax, maximum standardized uptake value; TBR, tumor-to-blood pool ratio of the SUV; TLR, tumor-to-liver ratio of the SUV.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Recent studies have identified several predictive markers obtained from non/mini-invasive methods have a promising role in screening for IPMNs, such as CA19-9, CEA, circulating microvesicles, MUC5AC, and several long noncoding RNA (lncRNAs). [13][14][15] The rise of machine learning, which is the interplay between artificial intelligence and large datasets, generates a more accurate model of pancreatic cancer's genesis and development, which can analyze large-scale data from different settings and combine them into explorations for pancreatic cancer's etiology. [16] Rech et al used the lncRNA myeloid regulator Morrbid and unbiased random forest machine learning to build unique, contextual signatures for each therapeutic component, revealing multiple cellular mechanisms during treatment.…”
Section: Promoting Early Detection Of Pancreatic Cancermentioning
confidence: 99%
“…[8] Recent studies have identified several predictive markers obtained from non/mini-invasive methods have a promising role in screening for IPMNs, such as CA19-9, CEA, circulating microvesicles, MUC5AC, and several long noncoding RNA (lncRNAs). [13-15]…”
Section: Promoting Early Detection Of Pancreatic Cancermentioning
confidence: 99%
“…However, duodenocephalopancreatectomy is not a simple procedure and is associated with significant mortality and morbidity rates, as well as a marked reduction in quality of life. For this reason, it is essential to identify the risk factors associated with cancer in order to only perform this procedure in individuals at highest risk [ 9 ]. Outside of oncology, two other major chapters have sparked a revolution in gastroenterology in recent decades: biological drugs and the interaction of the microbiota in inflammatory bowel disease.…”
mentioning
confidence: 99%